2015
DOI: 10.17498/kdeniz.309391
|View full text |Cite
|
Sign up to set email alerts
|

Sinif Öğretmenleri̇ni̇n Organ Bağişi Tutumlarinin Farkli Deği̇şkenler Açisindan İncelenmesi̇

Abstract: ÖZETBu çalışmanın amacı, sınıf öğretmenlerinin organ bağışına yönelik tutumlarını incelemektir. Betimsel bir niteliğe sahip olan bu çalışmada tarama modeli kullanılmıştır. Bu amaçla Ardahan ilinde görev yapan 93 sınıf öğretmenine, bir grup demografik sorular ile birlikte organ bağışı tutum ölçeği uygulanmıştır. Araştırma bulgularından elde edilen sonuçlar incelendiğinde, sınıf öğretmenlerinin organ bağışı hakkında olumlu bir tutuma sahip oldukları sonucu elde edilmiştir. Öğretmenlerin organ bağışına yönelik tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…It was found out that the average openness to experience scores of doctoral graduate teachers are higher than those of master and bachelor's graduates, and the scores of master graduate teachers are higher than those of bachelor's graduates. Sevgi (2017) concluded that extraversion and openness to experience scores of teachers with master degree were higher than those of bachelor's graduates.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found out that the average openness to experience scores of doctoral graduate teachers are higher than those of master and bachelor's graduates, and the scores of master graduate teachers are higher than those of bachelor's graduates. Sevgi (2017) concluded that extraversion and openness to experience scores of teachers with master degree were higher than those of bachelor's graduates.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the research, it was concluded that personality types of branch teachers working in high schools in Çanakkale respectively were openness to experience, agreeableness, conscientiousness, extraversion and neuroticism. Sevgi (2017) in her research identified personality traits of teachers respectively as agreeableness, extraversion, openness to experience, conscientiousness, and neuroticism.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Günümüzde internetin artık yaşamımızın içinde olmasının ve kullanımın yaygınlaşmasının sonuçlarda etkili olduğu düşünülmektedir. Bazı çalışmalarda ise öncelikle televizyonun tercih edildiği bulunmuştur (12)(13)(14)(15). Organ bağışı ve nakli konusunda halkı aydınlatmak, doğru bilgiler sunmak ve organ mafyası, organ ticareti gibi haber değeri yüksek olan asılsız haberlerin olumsuz etkisini azaltmak amacıyla medya kuruluşlarına ve çalışanlarına çok büyük görevler düşmektedir (16)(17)(18) Çalışmamızda organ bağışında bulunmak isteyenler eğitim öncesinde %15,0, eğitim sonrasında ise %53,1 olarak bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified